2010
DOI: 10.3324/haematol.2010.031013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitatively different red cell/nucleated cell chimerism in patients with long-term, persistent hematopoietic mixed chimerism after bone marrow transplantation for thalassemia major or sickle cell disease

Abstract: BackgroundPersistent mixed chimerism represents a state in which recipient and donor cells stably co-exist after hematopoietic stem cell transplantation. However, since in most of the studies reported in literature the engraftment state was observed in the nucleated cells, in this study we determined the donor origin of the mature erythrocytes of patients with persistent mixed chimerism after transplantation for hemoglobinopathies. Results were compared with the engraftment state observed in singly picked out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 37 publications
2
108
0
2
Order By: Relevance
“…11 Up to now, it is not clear if the mechanisms inducing an immunological tolerance in patients with PMC might also influence a different maturation of the donor erythroid precursors after HSCT for hemoglobinopathies. However, the presence of a split chimerism between mature erythrocytes and their progenitors has been recently described in persistent mixed chimera patients 13,14 with a predominant erythroid engraftment in the peripheral blood, while the proportion of erythroid precursors (BFU-E-burst forming unit erythroid) colonies and nucleated cells of donor origin in the bone marrow were equivalent (Fig. 1).…”
Section: -3mentioning
confidence: 99%
“…11 Up to now, it is not clear if the mechanisms inducing an immunological tolerance in patients with PMC might also influence a different maturation of the donor erythroid precursors after HSCT for hemoglobinopathies. However, the presence of a split chimerism between mature erythrocytes and their progenitors has been recently described in persistent mixed chimera patients 13,14 with a predominant erythroid engraftment in the peripheral blood, while the proportion of erythroid precursors (BFU-E-burst forming unit erythroid) colonies and nucleated cells of donor origin in the bone marrow were equivalent (Fig. 1).…”
Section: -3mentioning
confidence: 99%
“…Moreover, by analyzing singularly picked-up burst-forming unit erythroid colonies, we showed that the proportion of donorderived erythroid precursors was equivalent to that observed in the mature nucleated cells, rather than that of the red blood cells. These results suggest that in patients characterized by the presence of PMC after HSCT, a selective advantage of the maturation of donor erythroid precursors might successfully contrast the problems associated with the recipient ineffective erythropoiesis (Andreani et al 2011b). …”
Section: Mixed Chimerism Following Hsct For Thalassemiamentioning
confidence: 91%
“…Mixed chimerism after nonmyeloablative HSCT has been found beneficial for both thalassemia and SCA patients, [76][77][78][79] where a limited percentage of engrafted donor cells may be sufficient to overcome disease phenotype. Thus, the rationale for lowerintensity conditioning is relevant, because of its ability to promote mixed tolerance and the decreased risk for transplant-related toxicity and mortality, which will open HSCT-curative treatment to more patients.…”
Section: Potential Application Of Megadose Hsct With Tcm Veto Cells Fmentioning
confidence: 99%